صعوبات إعداد مشروع التخرج التي واجهت طلبة قسم الإرشاد النفسي في كلية التربية من وجهة نظرهم - حمشو,أحمد (University of Eloued جامعة الوادي, 2024)
ملخص: هدف البحث إلى تحديد درجة صعوبات إعداد مشروع التخرج التي واجهت طلبة قسم الإرشاد النفسي في كلية التربية من وجهة نظرهم، ومعرفة الفروق وفق متغير الجنس. اتبع الباحث المنهج الوصفي المسحي، وأعدّ استبانة خاصة بالبحث، وسحب عينة عشوائية طبقية مكوّنة من /40/ طالبًا وطالبة في السنة الرابعة أنجَزوا مشاريع التخرج، وأظهرت نتائج البحث ما يأتي: • درجة الصعوبات المتعلقة بـ (مادة مناهج البحث، والمعالجة الإحصائية، والمدة المتاحة لإنجاز المشروع) مرتفعة. • درجة الصعوبات المتعلقة بـ (الجامعة، والمشرف، والإطار المنهجي، والمراجع والدراسات السابقة، والجانب التقني، والتوثيق، ونتائج مشروع التخرج، وأدوات البحث وتطبيقها، والعمل المشترك، والصعوبات الشخصية) متوسطة. • عدم وجود فروق دالّة إحصائيًا عند مستوى (0,05) بين متوسطي درجات أفراد عينة البحث في استبانة صعوبات إعداد مشروع التخرج (من حيث الدرجة الكلية ومعظم المجالات الفرعية) وفق متغير الجنس (ذكر، أنثى)، ووجود فروق دالّة إحصائيًا في مجال الصعوبات المتعلقة بالجانب التقني لصالح الإناث، ومجال الصعوبات الشخصية لصالح. Abstract: The aim of the research was to determine the degree of difficulties in preparing the graduation project that faced students of the Department of Psychological Counseling in the Faculty of Education from their point of view, and to know the differences according to the gender variable. The researcher followed the descriptive survey Methodology, prepared a questionnaire for the research, and drew a stratified random sample consisting of 40 male and female students in the fourth year who completed graduation projects. The search results showed the following: • The degree of the following difficulties is high: difficulties related to the research methods material, difficulties related to statistical processing, and difficulties related to the time available to complete the project. • The degree of the following difficulties is moderate: difficulties related to the university, difficulties related to the supervisor, difficulties related to the methodological framework, difficulties related to references and previous studies, difficulties related to the technical aspect, personal difficulties, difficulties related to documentation, difficulties related to the results of the graduation project, difficulties related to research tools and their application, and difficulties related to joint work. • There were no statistically significant differences at the level of (0.05) between the average scores of the research sample members in the questionnaire on difficulties in preparing the graduation project (in terms of the total score and most sub-fields) according to the gender variable (male, female), and there were statistically significant differences in the field of difficulties related to the technical aspect in favor of females, and in the field of personal difficulties in favor of males
Keywords: الإرشاد النفسي; مشروع التخرج; Graduation Project; Psychological Counseling